Immunization of chimpanzees confers protection against challenge with human immunodeficiency virus. - Girard, M (1991)
Sustained high titers of neutralizing antibodies were elicited in three chimpanzees after sequential injections of different human immunodeficiency virus 1 (HIV-1) antigen preparations derived from the HIV-1 BRU strain that included whole inactivated virus or purified recombinant proteins and then synthetic peptides identical to the major HIV-1 neutralizing epitope V3. The animals were challenged i.v. with 40 chimpanzee infectious doses (equivalent to 100 tissue culture 50% infectious doses) of a stock of HIV-1 IIIB isolate. After 6 mo of follow-up, all three animals appeared uninfected by serologic and virologic criteria, including polymerase chain reaction analysis and failure to isolate virus from peripheral blood lymphocytes, bone marrow, and lymph node tissue. Of two chimpanzees monitored for 1 yr, virus was isolated initially from one animal at 32 weeks, but the second chimpanzee was virus negative by all assays through 12 mo; the third animal has remained virus negative through 9 mo of follow-up. These results indicate that it is possible to elicit protection against, or significantly delay infection of, HIV-1 by immunization, thus laying the foundation for development of an HIV-1 vaccine.